2013
DOI: 10.1176/appi.ajp.2013.13020208r
|View full text |Cite
|
Sign up to set email alerts
|

Response to Chronis-Tuscano et al. and Arns and Strehl

Abstract: ADHD Guidelines Group: Nonpharmacological interventions for ADHD: systematic review and meta-analyses of randomized controlled trials of dietary and psychological treatments. Am J Psychiatry 2013; 170:275-289 2. Arns M, Heinrieh H, Strehl Ü: Evaluation of neurofeedbaek in ADHD: the long and winding road. Biol Psyehol (in press) 3. Steiner NJ, Sheldriek RC, Gotthelf D, Perrin EC: Computer-based attention training in the sehools for ehildren with attention defieit/hyperactivity disorder: a preliminary trial. Cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 8 publications
3
28
0
2
Order By: Relevance
“…Controlling for medication changes (through sensitivity analysis) was indeed considered important and part of the authors' protocol, 11 but required a larger number of probably blinded studies. 51 The lack of standards regarding neurofeedback protocols is even more problematic for the field. Controlled studies on the optimal frequency bands, scalp sites, feedback timings, and thresholds are largely lacking, and clinical practice is still based on early animal studies and divergent clinical experience without control.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…Controlling for medication changes (through sensitivity analysis) was indeed considered important and part of the authors' protocol, 11 but required a larger number of probably blinded studies. 51 The lack of standards regarding neurofeedback protocols is even more problematic for the field. Controlled studies on the optimal frequency bands, scalp sites, feedback timings, and thresholds are largely lacking, and clinical practice is still based on early animal studies and divergent clinical experience without control.…”
Section: Methodological Issuesmentioning
confidence: 99%
“…A recent meta-analysis regarding nonpharmacologic interventions for ADHD concluded that increased evidence is needed for both neurofeedback and CT interventions before they can be supported as treatments for ADHD. 27 The current study is novel for several reasons. The research team conducted the first in-school translational efficacy trial comparing neurofeedback, CT, and control conditions.…”
mentioning
confidence: 99%
“…The latest conducted Dutch RCT applying a RED was published in The Lancet [15] and was both applauded as N. Rommelse (&) Á J. Buitelaar Nijmegen, Netherlands e-mail: N.Lambregts-Rommelse@psy.umcn.nl well as criticized in scientific and public media [19][20][21]. It is thus far the largest study conducted of this kind, in ADHD patients not selected for an atopic constitution or presence/absence of comorbidities, and with a rigorous attempt to investigate possible immunological mechanisms underlying response to RED.…”
mentioning
confidence: 99%
“…Do they feel stigmatized and isolated since they have to obey strict rules and regulations about diet habits that will likely differ from those observed by their peers? A recent meta-analysis excluded the Dutch studies because the effect sizes were significanty larger than the other studies of this kind [21]. Excluding outliers in meta-analyses is not generally considered to be the standard approach as outliers may actually ''reveal patterns that may lead to new insights about study characteristics that could be acting as potential moderators, i.e.…”
mentioning
confidence: 99%